Neoconservative education policy and the case of the English Baccalaureate. Issue 5 (2nd September 2020) - Neumann, Eszter; Gewirtz, Sharon; Maguire, Meg; Towers, Emma
ABSTRACT: Conservativism has gained significant influence on education-policy making and debates about education in many Anglophone countries. While conservative educational governments have advanced some neoliberal governance trends, they have also introduced characteristic neoconservative education elements, notably in the area of curricular content. This article focuses on the impact of conservative ideology on curriculum and assessment policies in English secondary education and specifically explores schools' first reactions to the introduction of a policy initiative that is emblematic of neoconservatism, the English Baccalaureate. The empirical discussion relies on a mixed methods study on the reception of the latest assessment and curriculum policies in English secondary schools. The findings suggest that the current reforms are transforming school subject hierarchies, resource allocation across subjects, and what counts as knowledge in English secondary schools, and introducing a new culture of subject—and by implication, teacher and student—'worth'.